(untitled) (Journal of Governance and Development (JGD), 2023)
The underlying study focuses on Pollution Haven Hypothesis (PHH) from the trade perspective for the Association of South East Asian Nations (ASEAN) countries for the period 1989 -2015. The PHH claims that in open trade regime developing countries tend to specialize and export pollution-intensive goods. This study examines this proposition in the context of ASEAN versus United states of America (USA) trade. The results indicate that exports of pollution-intensive- goods from ASEAN countries to USA significantly contribute to the pollution thereby, delaying the turning point income level of the EKC in ASEAN countries. The study, therefore, concludes that world pollution cannot be tackled unless advanced countries do not curtail the consumption of pollution-intensive goods.